Comparison of serum oestrogen concentrations in post-menopausal women taking oestrone sulphate and oestradiol. Issue 6106 (21st January 1978) - Anderson, A B; Sklovsky, E; Sayers, L; Steele, P A; Turnbull, A C
Abstract : Mean serum concentrations of oestradiol-17beta, oestrone, and oestrone sulphate in postmenopausal women were the same when measured up to six hours after treatment with either piperazine oestrone sulphate 1.5 mg or oestradiol valerate 2 mg. Maximum concentrations of oestradiol were less than those of oestrone, but oestrone sulphate reached concentrations about 30 times higher than those of oestrone. The rapid conversion of oestradiol valerate to oestrone and oestrone sulphate does not support the suggestion that in menopausal women oestradiol is less likely to be associated with a risk of endometrial carcinoma than oestrone sulphate, since the two preparations appear to become identical after ingestion.